Les virus Caractéristiques, Classification et multiplication - BOUTOUBA, AMINA (My University, 2017)
Viruses exhibit great diversity in all their characteristics. In this document we give a definition of viruses then their characteristics that concern their genome (DNA or RNA and its polarity), their structure enveloped or naked, their mode of penetration (endocytosis, translocation and fusion) and their classification. We also describe the replication of their genome and the expression of their genes. The document was finalized by a brief review of the consequences of viral multiplication for the infected cell. All the chapters described have been enriched by examples of well know viruses.
Keywords: virus; génome; multiplication virale; cellule infectée; genome; viral multiplication; infected cell